Temperature Upshift Mostly but not Always Enhances the Growth of Vibrio Species: A Systematic Review - Sheikh, H. I.; Najiah, M.; Fadhlina, A.; Laith, A. A.; Nor, M. M.; Jalal, K. C. A.; Kasan, Nor Azman (Frontiers in Marine Science, 2022)
The spread of Vibrio spp. and the prevalence of vibriosis around the world are often correlated with global warming, especially an increase in sea surface temperature. However, many ecological and virulence factors also trigger the spread of Vibrio species, while vibriosis occurs at both low and high temperatures. Recent studies that focused on a single factor (e.g. temperature) and one species (e.g. V. vulnificus) also showed that single factors such as temperature were insufficient to explain the pathogenicity and virulence of Vibrio spp. In this review, we have compiled and discussed the existing literature on the effect of temperature on different growth and pathogenicity of Vibrio spp. A systematic literature search was conducted using Web of Science (WoS) and SCOPUS databases up to 1st January 2022. After applying the selection criteria, a final list of 111 articles was included in this review. We have found that only certain Vibrio spp. are positively impacted by the increase in temperature. The results showed that 47% of the articles reported an increase in growth with the increase in temperature, while 38% showed that the relationship is complex. Reduced growth (6%) and no effect (9%) were also reported. These results showed that most but not all Vibrio spp. were positively impacted by an increase in temperature. The results indicated that V. alginolyticus, V. cholerae, V. parahaemolyticus, and V. vulnificus are the biggest threats to human and animal wellbeing.